New waves of immigration to small towns and rural areas in Portugal - Fonseca, Maria Lucinda (2019)
In the last decade the geography of immigration to Portugal has undergone profound change. In particular there has been a diversification of sending countries, and Eastern Europe, especially the Ukraine, Moldova, Romania and Russia, has become a major origin of migrants. The majority have settled in the Lisbon Metropolitan Area, but there is dispersal to all parts of the country. This paper examines recent immigration trends to small towns and rural areas in Portugal and discusses its effects on regional development. The study is based upon the analysis of official data sources and interviews carried out in municipalities located in the Alentejo region. This region remains rural with a significant ageing population and is undergoing a process of demographic decline. Following the analysis of the settlement patterns and the integration of immigrants in the labour market, some remarks are made about future trends of immigration to rural regions experiencing population loss, and its impacts upon the regional development process.